Challenges Faced by Libyan Students from Non-English Majors in Speaking English - Hetham M Alfaitori Alajaili; Yusawinur Barella (Universitas Muhammadiyah Enrekang, 2023)
The aim of this research is to analyze the problems faced by non-English speaking students in speaking skills in English at the College of Medical Technology, Derna, Libya. The research methodology used includes surveys and interviews with a representative sample of students. The research findings indicate that there are several problems faced by students regarding speaking skills in English, which encompass linguistic and non-linguistic issues. In terms of linguistic issues, many students feel a lack of vocabulary mastery, inaccurate pronunciation, and grammar. In terms of non-linguistic issues, problems related to low motivation, habits, and mother tongue were found. Therefore, this research highlights the challenges faced by non-English speaking students in developing their speaking skills in English. These challenges include linguistic issues such as vocabulary, pronunciation, and grammar, as well as non-linguistic issues such as motivation, habits, and the influence of the mother tongue. By addressing these challenges, appropriate interventions can be implemented to improve the speaking skills of non-English speaking students at the College of Medical Technology, Derna, Libya. One effective way to improve speaking skills in English is by regularly practicing speaking with others. This can be done by finding friends or English learning groups to actively discuss, debate, or engage in dialogue in English. Additionally, watching English movies or TV shows with subtitles and then attempting to repeat or mimic the dialogue is also a good way to practice pronunciation and expand vocabulary.